Asean Investment and Civil Society in Improving Sustainable in South East Asia - M. Elfan Kaukab; Suwandono Suwandono (Islamic Studies Journal for Social Transformation, 2020)
Despite having rapid economic development, the ASEAN region is not completely stable and p eaceful. Conflicts have been going on since long before the ASEAN is established. They happen in Myanmar, Thailand, and Philippines. A smaller scale of conflict also takes place in Indonesia. The view that security comes first before the investment has made it difficult to achieve peace and stability based on economic instruments. In this article, the writer proposes a view that Foreign Direct Investment (FDI) can be utilized as an important instrument in boosting peace and stability provided that the civil society sustains it. Two case studies are presented to show the relationship between FDI, civil society, and peace development in the conflict area, Myanmar and Philippines. It is recommended that civil society actively makes efforts to encourage FDI to come to the conflict are and establish capital -intensive industries, especially in Rakhine and Mindanao.